The relationship of erythropoietin receptor expression and prognosis in glioblastoma multiforme patients. - ÇEVIK, Serdar; Kitis, SERKAN; KİTİŞ, SERKAN; EVRAN, Şevket; AKKAYA, Enes; TOSUNER, ZEYNEP; TOSUNER, ZEYNEP; HANIMOGLU, Hakan (My University, 2018)
Background: Glioblastoma multiforme (GBM) is the most common primary brain tumor characterized with poor prognosis and short survival. In addition to the standard treatment protocols, targeted molecular treatment options are under trial. In the recent trials, erythropoietin and erythropoietin receptor were found to be linked with the progression of GBM cells. Aim: In this study, we compared the expression of EPOR with survival in GBM patients with mortality. Materials and Methods: Twenty‑six patients operated for GBM in 2012–2014 were enrolled in this study. Tumor tissues were stained with EPOR, epidermal growth factor receptor, vascular endothelial growth factor, and assigned as (1+), (2+), and (3+) according to their immunohistochemical staining levels. The average postoperative follow‑up time was 9.3 months. Kaplan–Meier’s survival test and Spearman’s correlation test were used in statistical analysis. Results: EPOR 1(+) stained group showed a median survival of 8 months (95% confidence interval [CI]: 0.954–15.046). EPOR 2(+) stained group showed a median survival of 6 months (95% CI: 2.901–9.090) EPOR 3(+) stained group showed a median survival of 2 months (95% CI: 0.400–3.600). (Kaplan–Meier P = 0.002). Conclusion: These results portrayed that EPOR staining levels were inversely proportional with average survival time. In the future, specific inhibitors of this molecule could be used to form a novel treatment option for GBM.